Healthy Lifestyle Courseware for Elderly (i-Health) / Nordiana Zulkifli - Zulkifli, Nordiana (2015)
E-Leaming has become a widely accepted and very useful for user to learn in an effective way. Currently, the source of reference to learn about healthy lifestyle for elderly is from the book, article or information taken from the Internet. Sometimes it is hard for the elderly to understand about information provided in the article or book. This is because the information provided is lengthy and very complex to understand. No doubt, the elderly need a new medium for them to learn and improve their understanding. The use of multimedia elements such as text, audio, animation, image and video can help the elderly to understand better and learn quickly. In addition, it also can help to reduce in monitoring the information. ADDIE model and tools being used in the development phase are also discussed. The ADDIE model has five phases namely Analysis, Design, Development, Implementation and Evaluation. However in this project, Documentation phase is added and it is the last phase for this project that are being adapted from ADDIE model.